SOF, Airpower, and Special Operations Airmen: Limited by Our Own Imaginations. Issue 1 (2nd January 2016) - Newton, Richard; Searle, Thomas
Abstract : Special operations forces and airpower are the two most flexible, but least understood, elements of Western military power. Misunderstanding has led to missed opportunities which we can no longer afford as we face an expanding array of complex, dynamic threats with shrinking military resources. Integrating airpower and special operations has enormous untapped potential across the spectrum of conflict, and particularly in preventative situations, but only if airmen and special operators work together. Through the use of case studies the authors present examples of successful SOF-airpower integration, but remind the readers that these instances were ad hoc, not addressed in pre-war training and doctrine, and at times resisted by senior leadership from both camps. The article concludes with the suggestion that special operations airmen ought to be the "bridge" between the airpower and special operations communities while seeking opportunities to exploit the advantage airpower offers during peacetime engagement scenarios.